Clean and Healthy Living Behaviour Post-COVID-19: A Qualitative Study on FISIP USU Students - Adriansyah, Vicky Rifai; Zaluchu, Fotarisman (Talenta Publisher, 2025)
This study aims to analyze the clean and healthy living behaviour (PHBS) among students post-Covid-19 pandemic. The study employs a qualitative method with in-depth interviews to explore behavioural changes in maintaining hygiene and health after Covid-19 is no longer considered a pandemic. The results indicate that awareness and practice of PHBS among students have declined following the end of the pandemic. Factors contributing to this decline include habits, personal reasons, and social environment. The study suggests the need for more intensive health campaigns to promote PHBS among the younger generation to prevent the spread of other infectious diseases in the future.